EVALUASI ARBORETUM SYLVA INDONESIA PC UNTAN DAN PENDOPO GUBERNUR KALIMANTAN BARAT MENJADI HUTAN KOTA DI PONTIANAK KOTA - Oktebriyani, Putri Nurul; Dewantara, Iswan; Erianto, . (JURNAL HUTAN LESTARI, 2019)
Evaluation of urban forest trees species is carried out with the aim the types of trees species that have been planted as an appropriate type in accordance with the functions and supporting development of urban forests. Supporting management urban forests in the future, spatial data of trees species is needed. This study aims to (1) to obtain the types and trees compiler in urban forest (2) to evaluation the suitability of treescompiler in urban forests (3) to determine the position of existing trees species in urban forests. This study used survey and identification method to determine the types of urban forest and the existing trees species. Assessment the suitability of tree species is based on the place of growth and literature study. Data analysis is conducted by considering silvicultural, management and aesthetic requirements. Based on this criteria are made that is appropriate, quite appropriate and not appropriate. The results showed that trees species compiler in Arboretum there are 35species of tree and in the West Borneo Governor's Pavilionthere are17species of tree that have appropriate criteria, there are 3 tree species that have quite approriate based on silvicultural, management and aesthetic requirements.Keyword : evaluation, tree, urban forest